2015
DOI: 10.17221/8245-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Effects of semen sexing kits (Heiferplus<sup>TM</sup> and Bullplus<sup>TM</sup>) supplemented to frozen-thawed bull semen on pregnancy rates, foetal sex ratios and selected reproductive parameters in cows

Abstract: It has been claimed that artificial insemination (AI) of cows with frozen-thawed semen treated with commercially produced kits, Heiferplus TM (HP, in favour of female gender) and Bullplus TM (BP, in favour of male gender), increases the birth chance of calves with desired sex ratio by at least 20-25% and pregnancy rates by at least 5-20%. Hence, this study was conducted to investigate the efficacy of HP and BP kits as combined with AI on the pregnancy rates, foetal sex ratios and some reproductive parameters i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 3 publications
1
0
0
Order By: Relevance
“…The result of statistical analysis indicated that the semen type was not a significant predictor of twining rate. Similar to our findings, Healy et al (2013) and Turk et al (2015) reported that the incidence of twins insignificantly influenced by the semen sexing. Healy et al (2013) demonstrated that heavier heifers were significantly more prone to twining.…”
Section: Twiningsupporting
confidence: 92%
“…The result of statistical analysis indicated that the semen type was not a significant predictor of twining rate. Similar to our findings, Healy et al (2013) and Turk et al (2015) reported that the incidence of twins insignificantly influenced by the semen sexing. Healy et al (2013) demonstrated that heavier heifers were significantly more prone to twining.…”
Section: Twiningsupporting
confidence: 92%